Nature and effectiveness of extension services provided by producers organization - Nikam, Vinayak; Singh, Premlata; ., Satyapriya; Sharma, D.K. (Annals of Agricultural Research, 2016)
Mahagrapes was established in the year 1991 as marketing partner to grapes growers' cooperative.Many studies indicate that it has helped grape growers from Maharashtra to increase their incomeand export competitiveness by providing good extension services to the members. Therefore studywas conducted to study the nature and effectiveness of services of Mahagrapes with 90 grapesgrowers who were members of cooperatives linked to Mahagrapes from Nashik, Sangli and Punedistricts of Maharashtra. Data were collected through focused group discussion and personalinterview of the farmers. Regarding nature of extension services of Mahagrapes it was found thatMahagrapes provided biobased pesticides to the members. Mahagrapes consultants providedconsultancy services about Good Agricultural Practices (GAP) standards, cultural practices,weather, harvesting etc. Mahagrapes provided all support during marketing operations likegrading, packaging, transport cooling and storage. It also was involved in extension activitieslike demonstrations, trainings, group meetings and farm tours. Overall effectiveness index scorewith indicators satisfaction, knowledge and adoption was 92.34 percent indicating higheffectiveness of services. Thus, quality and effective services provided by the producers'organizations have direct bearing on the success of organization and satisfaction of the members